2013
DOI: 10.1302/2046-3758.22.2000092
|View full text |Cite
|
Sign up to set email alerts
|

Matrix assisted autologous chondrocyte transplantation for cartilage treatment

Abstract: ObjectivesMatrix-assisted autologous chondrocyte transplantation (MACT) has been developed and applied in the clinical practice in the last decade to overcome most of the disadvantages of the first generation procedures. The purpose of this systematic review is to document and analyse the available literature on the results of MACT in the treatment of chondral and osteochondral lesions of the knee.MethodsAll studies published in English addressing MACT procedures were identified, including those that fulfilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 74 publications
0
71
0
2
Order By: Relevance
“…The alizarin Red staining procedure for calcium precipitation (mineralization) was as follows (1). Fix cells in 2.5% glutaraldehyde (freshly prepared in 1× PBS buffer) for 10-15 minutes at room temperature (2). Remove the fixation solution, and wash cells with 1× PBS (pH adjusted to 4.2) 1-2 times (3).…”
Section: Osteogenic Induction Of Hbascsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alizarin Red staining procedure for calcium precipitation (mineralization) was as follows (1). Fix cells in 2.5% glutaraldehyde (freshly prepared in 1× PBS buffer) for 10-15 minutes at room temperature (2). Remove the fixation solution, and wash cells with 1× PBS (pH adjusted to 4.2) 1-2 times (3).…”
Section: Osteogenic Induction Of Hbascsmentioning
confidence: 99%
“…This technique consists of three main steps, including the isolation of chondrocytes from healthy cartilage tissue, chondrocyte cultivation or expansion in vitro over 2-3 weeks, and re-injection of chondrocytes into the injured cartilage, covered with a periosteal flap [1]. This method gained international acceptance within the orthopedic surgery field [2,3] and was further refined by adding biomaterials such as coated scaffolds, membranes, and different matrices [4,5]. Despite this wide acceptance, several studies have revealed certain problems and limitations of ACT, including cell leakage, the requirement for high cell concentrations, and apoptosis of the re-injected chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of microfracture, this is referred to as autologous matrix-(or collagen-)induced chondrogenesis [11,37] and, in the setting of chondrocyte implantation, is known as matrix-assisted chondrocyte transplantation or second-/third-generation autologous chondrocyte transplantation, which is not currently available in the United States [20]. These biologic matrices are composed of cartilage extracellular matrix molecules or biopolymers that function as a scaffold for marrow components or transplanted chondrocytes to form more hyaline-like repair tissue in articular cartilage defects [35].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Superficial cartilage defects have mainly been treated with hyaluronic acid (HA), while chondral and osteochondral lesions have been medicated by means of HA and autologous cartilage transplantation (ACT) since 1994. [19][20][21][22][23] In the latter case, the use of matrixassisted autologous chondrocyte transplantation has become increasingly attractive since 1998, because articular cartilage defects of varying degrees can be replenished more easily and in a more targeted manner. 22,24 So far, a variety of different synthetic and natural materials have been investigated with respect to cartilage repair.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] In the latter case, the use of matrixassisted autologous chondrocyte transplantation has become increasingly attractive since 1998, because articular cartilage defects of varying degrees can be replenished more easily and in a more targeted manner. 22,24 So far, a variety of different synthetic and natural materials have been investigated with respect to cartilage repair. 3,25 The main focus lies on restoring the complex structure and properties of hyaline cartilage to achieve long-term improvements in cartilage engineering.…”
Section: Introductionmentioning
confidence: 99%